Физическая модель процесса образования пакетов стружки при обработке материалов в свете общей математической модели процесса резания при глубоком сверлении - Плахотникова, Инна Борисовна; Маршуба, Вячеслав Павлович (НТУ "ХПИ", 2006)
It is offered the physical model for process of formation of chip scrap packages and fragments of chip buildup at processing of different materials depending on influencing the physical phenomena in the cutting area and tool zone. The offered physical model is destined to create the general mathematical model, which describes process of deep drilling in different materials. Usage of this physical model will allow determining necessary conditions for processing of deep holes with maximum productivity at processing the parts from different materials.
Keywords: инструмент режущий; нарост; явления физико-химические